DEVELOPMENT OF CHARACTER EDUCATION MODEL'S IN SCHOOLS - Tb. Ahmad Mahdi; Nopri Dwi Siswanto; Aan Hasanah; Bambang Samsul Arifin (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
Education in schools is still believed to be a very powerful medium in building the intelligence, skills and personality of students. School is a place that manages and organizes learning activities that have consistency of intensity and sustainability so that the transformation of knowledge becomes complete, developing the personality and character of students who breathe the noble values of the nation and religion. This study used a descriptive analysis method. This research describes the model of managing character education during a pandemic. This research uses secondary data sources, including the web, jumal, and books related to character education. The approach used in this study is qualitative. This qualitative data analysis consists of several activity flows, namely categorization, data reduction, data presentation and drawing conclusions. The development of character education in intensive schools is an effort to awaken and improve learning activities effectively in instilling values and character in every school citizen which includes aspects of knowledge, awareness or will and action in order to carry out values related to God Almighty, oneself, fellow human beings, environment and nationality, so that it is expected to become a generation of quality actions, morality, faith and piety in real life as an Indonesian citizen.